Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1967
DOI: 10.1266/jjg.42.121
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF X-RAY IRRADIATION ON SELECTION RESPONSE IN <i>ôDROSOPHILA MELANOGASTER</i>

Abstract: One of the most important problems in population genetics concerns how much genetic variation can be induced in the polygenic systems of various organisms by exposure to radiation, and the extent to which this variation affects the process of organic evolution. However, works dealing with spontaneous or induced mutations in polygenic systems in animals as well as in plants are rather few. Buzzati-Traverso (1953) reported in Drosophila that new variation induced by X-rays in polygenic systems can be utilized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1968
1968
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…It seems unlikely therefore that induced mutation rates per locus are higher for polygenes than major genes (cf. Burdick and Mukai, 1958;Mukai, 1964), a conclusion also supported by the work of Kitagawa (1967). It must be admitted that maternal influences may have led to an overestimate of the doubling dose in the present experiments and it is possible that the seeds used had greater inherent radioresistance than those used by Robbelen and Veleminsky et al by virtue of different genotype or conditions of treatment.…”
Section: Resultssupporting
confidence: 63%
“…It seems unlikely therefore that induced mutation rates per locus are higher for polygenes than major genes (cf. Burdick and Mukai, 1958;Mukai, 1964), a conclusion also supported by the work of Kitagawa (1967). It must be admitted that maternal influences may have led to an overestimate of the doubling dose in the present experiments and it is possible that the seeds used had greater inherent radioresistance than those used by Robbelen and Veleminsky et al by virtue of different genotype or conditions of treatment.…”
Section: Resultssupporting
confidence: 63%
“…Second, it may help in finding out more about the nature of variation in quantitative traits, and their relationship to natural selection and evolution. Clayton & Robertson (1955), Kitagawa (1967) and Hollingdale & Barker (1971) showed that radiation increased mutation rate and hence response to selection in inbred lines of Drosophila. However it is considered (Enfield, 1986) that radiation is likely to produce a class of mutations skewed in the unfavourable direction, so radiation treatments are likely to provide only limited information about the contribution of naturally occurring mutations to response to selection.…”
Section: Introductionmentioning
confidence: 99%